Proceedings of the SIGCHI Conference on Human Factors in Computing Systems Changing Our World, Changing Ourselves - CHI '02 2002
DOI: 10.1145/503425.503428
|View full text |Cite
|
Sign up to set email alerts
|

Gestural and audio metaphors as a means of control for mobile devices

Abstract: This paper discusses the use of gesture and non-speech audio as ways to improve the user interface of a mobile music player. Their key advantages mean that users could use a player without having to look at its controls when on the move. Two very different evaluations of the player took place: one based on a standard usability experiment (comparing the new player to a standard design) and the other a video analysis of the player in use. Both of these showed significant usability improvements for the gesture/au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(146 citation statements)
references
References 8 publications
1
141
0
4
Order By: Relevance
“…229 Non-visual interfaces, particularly audio display 230 interfaces have been shown to be effective in improv-231 ing interaction and integration within existing physical 232 contexts. For example, Brewster and Pirhonen [21,22] 233 have explored the combination of gesture and audio 234 display that allows for complicated interaction with 235 mobile devices while people are in motion. The Audio 236 Aura project [23] explores how to better connect hu-237 man activity in the physical world with virtual infor-238 mation through use of audio display.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…229 Non-visual interfaces, particularly audio display 230 interfaces have been shown to be effective in improv-231 ing interaction and integration within existing physical 232 contexts. For example, Brewster and Pirhonen [21,22] 233 have explored the combination of gesture and audio 234 display that allows for complicated interaction with 235 mobile devices while people are in motion. The Audio 236 Aura project [23] explores how to better connect hu-237 man activity in the physical world with virtual infor-238 mation through use of audio display.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…to keep the experimental conditions consistent and not introduce noise in the results. As an alternative, researchers have replicated real world settings by creating walking routes indoors [3,14,25] and outdoors [5,12,13] for users to navigate. Some studies [3,14,15] have also added obstacles to the walking path to increase the user's cognitive workload.…”
Section: The Effects Of Mobilitymentioning
confidence: 99%
“…In previous studies, two broad methods have been used to examine the effects of mobility on input performance with handheld devices: 1) walking on a treadmill [3,4] and 2) walking around a predefined route [3,13,25]. Barnard et al [3] compared both methods and reported the advantages and limitations of each to examine the impact of walking on interactions with mobile devices.…”
Section: Introductionmentioning
confidence: 99%
“…Touch: On mobile touch-based devices, sweeping and tapping the screen can let the user control a music player without looking at the UI [27]. Döring et al [12] adapted this interaction style for cars on a touch-sensitive steering wheel and reduced visual demand during interaction.…”
Section: User Interfaces For Audio Player Controlmentioning
confidence: 99%